PENYULUHAN TENTANG PEMANFAATAN OBAT TRADISIONAL (JAHE MERAH, KAYU MANIS DAN GULA MERAH) TERHADAP PENINGKATAN IMMUNITAS DALAM MENGHADAPI COVID-19 PADA SISWA KELAS XII SEKOLAH KEJURUAN YAYASAN PERGURUAN INDONESIA MEMBANGUN (YAPIM) - Sri Sudewi Sitio; Bunga Rimta Barus; Bahtera Bin David Purba; Yunita Syahputi Damanik; Dian Fachrummisa (INSTITUT KESEHATAN DELI HUSADA, 2021)
Senior high school students are young adults who are very active and have broad interactions between each other and their families so that this age group has the potential to become carriers in the transmission of Covid-19. For this reason, this age group needs to build its immune system through various efforts to live healthy behaviors including consuming ingredients / foods that can increase the body's immunity, there are many natural resources in the form of spices that can be used as basic ingredients for making drinks that are useful for increasing body immunity in the body. during the Covid-19 pandemic. The existence of spice plants (red ginger, cinnamon, and brown sugar) which are commonly planted by residents around Deli Tua. Red Ginger contains curcuminoid compounds which function as immunostimulators in boosting the immune system. In addition, spices such as cinnamon and brown sugar contain antioxidants that are high enough to ward off free radicals in our bodies. Community service activities were carried out at the Vocational School of the Indonesian Build Education Foundation (YAPIM) by providing education and lectures to class XII students regarding processing red ginger, cinnamon and brown sugar. The purpose of this service is to provide information about the processing of red ginger, cinnamon and brown sugar into traditional drinks that can increase the body's immunity in the face of the Covid-19 pandemic. The service was carried out by providing an explanation of the stages of the manufacturing process, then continued with direct practice. The results of this community service are in the form of traditional drinks made from red ginger, cinnamon and brown sugar which are expected to increase the immunity of students and the community, then increase knowledge and skills in processing red ginger, cinnamon and brown sugar, especially for extension participants.